Political determinants of e-government performance revisited: comparing democracies and autocracies - Stier, Sebastian (Government information quarterly, 2015)
While the literature analyzing the cross-national determinants of e-government performance reports robust results for structural variables, the level of agreement regarding political factors remains low. Deriving theories from comparative political science, this article hypothesizes how regime type and government capacity determine the global variation in e-government. Methodologically, the paper adds several points to improve accuracy in statistical analyses using the United Nations E-Government Development Index, which have often been afflicted by improper model specifications. Empirically, all seven editions of the index are tested under a common framework in cross-sectional regression analyses, revealing several interdependent trends. While the innovation-friendly environment of democracies was the primary political source of e-government development, autocracies are catching up in order to enhance pro-regime activism on the internet and legitimize their rule by improving economic performance. Government capacity also grows in importance, as e-government programs have become more technologically sophisticated.
Gesehen am 23.06.2020